DEVELOPMENT OF HERITAGE E.I. KOLBASINA ON INTRODUCTION OF NON\TRADITIONAL CROPS IN THE CENTRAL REGION OF THE RUSSIAN FEDERATION - A. Y. Pavlova; F. Y. Polikarpova; N. V. Kozak; N. Y. Jura; E. A. Tut; S. A. Salimova (Овощи России, 2015)
The main direction of half a century of scientific activity of Dr. biol. of Sc. E.I. Kolbasina were the introduction of the Central Region of the Russian the Far Eastern and the study of fruit lianas: Actinidia and Schisandrachinensis.